PENERAPAN MODEL STUDENT TEAMS ACHIEVIEMENT DIVISIONS (STAD) PADA PEMBELAJARAN IPS SISWA KELAS IV SD NEGERI 2 PETUNANG - Miko Yensi; Andriana Sofiarini; Andri Valen (LP4MK STKIP PGRI Lubuklinggau, 2022)
The research objective was to find out using the Student Teams Achieviement Divisions model in social studies learning for grade IV Elementary School 2 Petunang students significantly complete. The research method used was quasi-experimental, the research design was pretest-posttest group design. The population was all students in grade IV Elementary School 2 Petunang and a sample of 22 students in grade IV which was determined by simple random sampling. The data collection technique used a test technique in the form of 7 essay questions. The average final test score of students was 76.62 with the percentage of the number of students who completed 59.09%. The collected data were analyzed using the t test. based on the results of t-test analysis at a significant level α = 0.05, the value obtained is tcount (1.93) ≥ t_ (table) (1.72), because tcount ≥ t_ (table), it can be concluded that the social studies learning outcomes of students use The Students Teams Achieviement Divisions' learning model was significantly complete. Keywords: Model Student Teams Achieviement Divisions, Social Studies Learning, Learning Outcomes.